Evaluation of IPM modules for management of sucking and borer insect pest complex of mungbean in Odisha - Sasmal, Arundhati (Indian Journal of Plant Protection, 2018)
Field experiments were conducted to evaluate four different integrated insect pest management (IPM) modules to control sucking and borer insect pest complex in mungbean variety OUM 11-5 (Kamadev) duringKharif, 2014-15 and 2015-16 at Centre for Pulses Research, OUAT, Berhampur, Odisha. The IPM module including ‘seed treatment with imidacloprid 600 FS @ 5 ml/kg seed, installation of yellow sticky trap @100/ha, foliar spray of NSKE 5% spray at 30 DAS and foliar spray of indoxacarb 14.5% EC @ 500 ml/ha at 45 DAS’ was found to be superior than other modules with respect to the insect pest incidence, yield maximization and economy. Both sucking and borer insect pests were kept under threshold limit and the average yield was highest (8.3q/ha) with maximum beneft cost ratio (2.42) in the said IPM module.